Ontogenetic Features of Halo Accumulation of Certain Hemigalophytes Under the Conditions of Karakalpakstan - Davletmuratova Venera Begdullaevna; Serekeeva Gulayim Abdugalievna; Begjanova Gulnara Turdimuxanbetova (International Journal on Orange Technologies, 2021)
This work is devoted to the ontogenetic features of haloaccumulation of some hemihalophytes in the conditions of Karakalpakstan. The work revealed quantitative and qualitative indicators of haloaccumulation as the development phases of the studied plants progressed: Atriplex tatarica L., Zygophyllum oxianum Boriss., Elaeagnus turcomanica N. Kozl. The change in the content of mineral salts in the leaves of hemihalophytes was investigated. The results of the study showed that different species differ in qualitative and quantitative indicators of haloaccumulation by developmental phases, but the studied species have a single regularity of haloaccumulation intensity: in the initial phases it is low, reaching a maximum during the period of intensive growth and formation of vegetative and generative organs; drops sharply in the flowering phase, increases again at the fruiting stage and gradually decreases towards the end of the growing season as the growth processes diminish.